2020
DOI: 10.1371/journal.pone.0234250
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid comparison of four sympatric loliginid squids in the northern South China Sea: Indication for their similar feeding strategy

Abstract: Feeding strategies of sympatric squid species help to understand their role in marine ecosystems. Four loliginid squids, Uroteuthis duvaucelii, Uroteuthis edulis, Uroteuthis chinensis, and Loliolus uyii are the major cephalopod species in the coastal waters of the northern South China Sea, where they occur together. We investigated their feeding strategies in terms of foraging behavior and habitat use by comparing fatty acid profiles and spatial distributions. There were no significant differences in the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The differentiation of trophic niches can be a sign of interspecific feeding differences and habitat differentiation (Gao et al, 2018). Interspecific spatial isolation is an effective method of alleviating competition for food resources (Lin et al, 2020). fish diet significant affected the tropic niche width of M. terminalis.…”
Section: Dietary Niche Diversificationmentioning
confidence: 99%
“…The differentiation of trophic niches can be a sign of interspecific feeding differences and habitat differentiation (Gao et al, 2018). Interspecific spatial isolation is an effective method of alleviating competition for food resources (Lin et al, 2020). fish diet significant affected the tropic niche width of M. terminalis.…”
Section: Dietary Niche Diversificationmentioning
confidence: 99%
“…Studies on habitat utilization and feeding behavior of four different species of squid (U. duvaucelii, U. edulis, U. chinensis and Loliolus uyii) in the northern SCS showed that although the feeding strategy was similar, their habitats did not overlap. This spatial segregation could reduce their competition for resources and buffer their trophic interactions, thus increasing the possibility of the species coexisting in the region [22].…”
Section: Relationship Between U Chinensis and Cftmentioning
confidence: 99%
“…The available studies on the U. chinensis in the SCS are all focused on biological characteristics [18][19][20], migration the catch of Ommastrephes bartramii in the northwestern Pacific to a great extent [16,17]. The available studies on the U. chinensis in the SCS are all focused on biological characteristics [18][19][20], migration characteristics [21], feeding behavior [22], and resource status [23]. Studies showed that U. chinensis did not migrate on a large scale, but moved in short distances according to local water temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we used fatty acid analysis to investigate the variability of feeding strategies and trophic niche among these three groups off the Peruvian exclusive economic zone. As the fatty acids of a heterotrophic organism effectively reflect those in its diet [37], this study was designed to (1) determine the differences in fatty acid composition and trophic niche among three groups, (2) explore the variability of fatty acid composition between sexes, and (3) evaluate the feeding strategy of three groups of D. gigas. This study provides the basis for understanding the variability of feeding strategy and coexistence mechanism among groups and sexes.…”
Section: Introductionmentioning
confidence: 99%